Ecological-Economic Analysis and Valuation of Biodiversity - Paulo A.L.D. Nunes; Jeroen C.J.M. van den Bergh; Peter Nijkamp (Tinbergen Institute, 2000)
This paper introduces and surveys ecological-economic analysis ofbiodiversity. It seeks to identify the complex linkages betweeneconomic and ecological systems with a view to a solid exploration ofvaluation issues in biodiversity. Against this background the studyoffers a review of key ecological concepts that are essential inbuilding bridges between ecology and economics. Issues discussed hereare ecosystem management principles, biodiversity indices and modernconcepts such as resilience. Particular attention is given to variousmonetary valuation approaches and methods, from the perspective ofconservation and sustainable use of biodiversity. For this purpose,the interrelation between biodiversity, resources, ecosystemfunctions, and human welfare is examined. The use of ecological andvalue indicators in integrated modelling and analysis is alsoaddressed. Finally, several illustrative applications are presentedin order to demonstrate the usefulness of the approaches discussed.Ultimately, this study offers a basis for biodiversity valuationapproaches at the interface of economics and ecology.
Keywords: 330; Artenvielfalt; Umweltökonomik; Theorie